Using National Drug Codes and drug knowledge bases to organize prescription records from multiple sources. - Simonaitis L; McDonald CJ (American Journal of Health-System Pharmacy, 2009)
PURPOSE: The utility of National Drug Codes (NDCs) and drug knowledge bases (DKBs) in the organization of prescription records from multiple sources was studied. METHODS: The master files of most pharmacy systems include NDCs and local codes to identify the products they dispense. We obtained a large sample of prescription records from seven different sources. These records carried a national product code or a local code that could be translated into a national product code via their formulary master. We obtained mapping tables from five DKBs. We measured the degree to which the DKB mapping tables covered the national product codes carried in or associated with the sample of prescription records. RESULTS: Considering the total prescription volume, DKBs covered 93.0-99.8% of the product codes from three outpatient sources and 77.4-97.0% of the product codes from four inpatient sources. Among the in-patient sources, invented codes explained 36-94% of the noncoverage. Outpatient pharmacy sources rarely invented codes, which comprised only 0.11-0.21% of their total prescription volume, compared with inpatient pharmacy sources for which invented codes comprised 1.7-7.4% of their prescription volume. The distribution of prescribed products was highly skewed, with 1.4-4.4% of codes accounting for 50% of the message volume and 10.7-34.5% accounting for 90% of the message volume. CONCLUSION: DKBs cover the product codes used by outpatient sources sufficiently well to permit automatic mapping. Changes in policies and standards could increase coverage of product codes used by inpatient sources.